Comorbidities in patients with Unverricht-Lundborg disease (EPM1) - Sipilä Jussi OT; Kälviäinen Reetta (WILEY, 2022)
Background: Unverricht-Lundborg disease (EPM1) typically leads to accumulating disability. Disability may also be caused by comorbidities but there are no data available on these.
Aims of the study: To investigate the frequency of comorbidities in EPM1.
Methods: Comorbidity data of a previously described cohort of 135 Finnish patients with EPM1 were retrieved from neurological, surgical (including subspecialities), internal medicine (including subspecialities) and intensive care patient charts of the treating hospitals.
Results: Mean follow-up time was 31.4 years (SD 12.4 years, range 6.8-57.8 years), during which at least one comorbidity was observed in 107 patients (79%) and three or more in 53 (39%). The most common diagnostic categories were external injuries, mental and behavioural disorders and endocrine, nutritional and metabolic diseases. The most common single comorbid diagnosis was a fracture of the ankle (in 19% of all patients). The second most common single comorbid diagnosis in the cohort was diabetes (in 13% of all patients), and the third was depression, recorded for 13% of the cohort. Malignancies and cardiovascular end-organ damage were rare, whereas phimosis/paraphimosis appeared more common than in general population.
Conclusions: Patients with EPM1 often have comorbidities. Trauma and mental health risks should be especially followed and acted upon. Further studies are needed to more accurately comorbidity risks, characteristics and patient needs.